Incidence of Rota Virus Gastroenteritis Among Children Below 5 years with Diarrhea - Aravind, Arun; R Latha (Asian Journal of Medical Research, 2021)
Background: Diarrheal illness had a huge impact globally as it became the third most common cause of death in children younger than 5 years, accounting for almost 1.5 million deaths annually or 18% of all deaths in this age group death taking the greatest toll in developing countries. This study is being conducted to study the incidence of Rota virus gastroenteritis among children below 5 years with diarrhea. Subjects and Methods: Stool samples from children <5years with watery diarrhea were enrolled in the study. Immediately after stool collection it was transported to the lab and iodine and saline wet mount was done to rule out any parasites. The sample were also processed in special media like Wilson blair and alkaline peptone water to rule out vibrio cholera, Tetrathionate broth to culture salmonella and Selenite F Broth for salmonella and shigella, Deoxycholate citrate agar. Then sample was collected and stored in the refrigerator. All the samples despite the presence or absence of other enteropathogens were tested for Rota virus. Results: 129 cases of diarrhea were included in the study of which 71 ie. 55% was Rota virus positive. Among the 71 Rota virus positive cases 65% were males and 35% were females. There were 21 male and 12 female bacterial cases. Salmonella was identified in 20 (60%) and shigella in 13 (40%) of cases. Conclusion: The study conducted here has shown that 55% of the 129 diarrheal cases included in the study was due to rota virus infection. The study shows that number of bacterial and parasitic infection are less compared to rota virus infection and more over it can be treated with medication and severity of diarrhea and dehydration is also not as high as seen in case of rota virus infection.